2015
DOI: 10.3109/13880209.2015.1087036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macamides on endurance capacity and anti-fatigue property in prolonged swimming mice

Abstract: Objective: The present study investigates the effects of macamides on endurance capacity and antifatigue property in prolonged swimming mice. Materials and methods: The Balb/c mice were divided into seven groups: a control group, low-dose groups of N-benzyllinoleamide, N-benzyloleamide, and N-benzylpalmitamide, high-dose groups of these macamides. The macamides groups received the commercial products (12 and 40 mg/kg, ig), while the control group received vehicle for 21 d. On the 14th day, the mice were given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…Yang et al . reported that N ‐benzyloleamide (40 mg kg −1 ), one of the macamide monomers, had pharmaceutical properties that acted against exercise‐induced fatigue . All the above studies proved to have a beneficial effect of macamides on anti‐fatigue.…”
Section: Introductionmentioning
confidence: 90%
“…Yang et al . reported that N ‐benzyloleamide (40 mg kg −1 ), one of the macamide monomers, had pharmaceutical properties that acted against exercise‐induced fatigue . All the above studies proved to have a beneficial effect of macamides on anti‐fatigue.…”
Section: Introductionmentioning
confidence: 90%
“…However, ARGI+ in combination with Multi Maca supplementation more influences aerobic capacity (p = 0,047 and p = 0,048). According toYang Q et al (2016) [32] compared with the control group of mice, exhaustive swimming time was significantly prolonged in group which used a high-dose of Maca. Very important information about the effect of Maca influence indicates J.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, macamide has been proposed to be the biologically active substance, because of its multiple functions, such as fatty acid amide hydrolase inhibitor [5], improving sexual performance [6], endurance capacity and antifatigue [7]. So far, 22 kinds of macamide is separated and identified from Maca tuber, and N-3-methoxybenzyl-palmitamide (MPM) is a representative substance [8,9].…”
Section: Introductionmentioning
confidence: 99%